Flowering induction in mango tree: Updates, perspectives and options for organic agriculture - Prates, Adrielle Rodrigues [UNESP]; Züge, Patrícia Graosque Ulguim [UNESP]; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevêdo; De Ávila, Jorgiani [UNESP] (FapUNIFESP (SciELO), 2021)
The artificial flowering induction in mango tree is the most important crop management in mango orchards and requires greater attention from growers. The management involves three steps: Stoppage of plant growth, branch maturation and flowering induction with nitrates. The first stage starts with the application of paclobutrazol to the soil. However, problems with the use of excessive concentrations are common and lead to the accumulation of residues in the soil. In addition, the use of paclobutrazol is not allowed in organic agriculture. Therefore, this review article aimed to compile information about the updates and efforts to solve these problems in conventional mango crops, as well as identify alternatives for its organic management. In conventional orchards, the application of fulvic acids in association with paclobutrazol, as an alternative to the single use of paclobutrazol, was identified as a way to improve the absorption of the product by plants and, consequently, reduce the concentrations and residues in the soil. Researches involving pruning, girdling, fertilization and irrigation should be developed as an alternative to the use of paclobutrazol for the organic crop system of mango cultivars in tropical and subtropical regions.
Indução ao florescimento em mangueira: Atualidades, perspectivas e opções para o sistema orgânico
Keywords: Drought stress; Mineral nutrition; Plant regulators; Sustainable cultivation